2015
DOI: 10.1007/s11136-015-1191-4
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Renal Quality of Life Profile scores in routine clinical practice: an aid to treatment decision-making

Abstract: The proposed categorization of the RQLP will aid the clinical interpretation of change in RQLP score informing treatment decision-making in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…First, despite the assigned scores being constructed based on minimal importance, the anchor‐based approaches may be limited by the distribution of scores within each set of the anchor question to detect the clinical significance . Although the anchor questions used in this study have been well‐validated and have been widely used in both nephrology and dermatology HRQOL research, it can be challenging if the credibility and certainty of the anchor question are doubtful as appropriate indicators . Currently, the pruritus‐specific QOL instruments are available such as the ItchyQoL and Pruritus‐related Life Quality Index .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, despite the assigned scores being constructed based on minimal importance, the anchor‐based approaches may be limited by the distribution of scores within each set of the anchor question to detect the clinical significance . Although the anchor questions used in this study have been well‐validated and have been widely used in both nephrology and dermatology HRQOL research, it can be challenging if the credibility and certainty of the anchor question are doubtful as appropriate indicators . Currently, the pruritus‐specific QOL instruments are available such as the ItchyQoL and Pruritus‐related Life Quality Index .…”
Section: Discussionmentioning
confidence: 99%
“…The banding of DLQI scores on quality of life has been proposed: no effect (0–1 points), small effect (2–5 points), moderate effect (6–10 points), very large effect (11–20 points) and extremely large effect (21–30 points) The global impact of kidney disease on quality of life, one question evaluating the impact of the kidney disease on overall impairment of HRQOL using the 5‐point numerical rating scale ranges from 0 to 4 with 0 being no effect, and 4 being extremely large effect . This anchor‐based question was given to 25 dialysis patients to address on readability, the clarity of the direction and response choices of the questionnaire. …”
Section: Methodsmentioning
confidence: 99%
“…Description of the 20 items suggested by the 13 participants Appendix 1 Quotes from participants illustrating each concept Table 1. The 20 descriptors, given in five categories, of the 108 items mentioned by the 13 participants (median number of items mentioned per participant = 8, range [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Van Cranenburgh et al identified why HRQoL assessment is relevant for dermatologic practice and which patients would benefit most from routine HRQoL assessment. Aawar et al suggested that using a patient's QoL information can lead to optimized treatment decision making, and be used to prioritize problems, facilitate communication, screen for potential risks, identify preferences and monitor response to treatment. Other potential benefits are in the training of new staff, in clinical audit and for clinical governance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation